Monitoring leakage in water pipe installation using a water flow sensor - Prima, Delta Ardy; Atthariq, Atthariq; Parenreng, Jumadi Mabe (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
The need for water for humans is the main thing and cannot be replaced with anything else. Water will always be needed every time for consumption and daily activities. Therefore, the need for water is always considered in the distribution process so that every community can meet its water needs. Especially residential areas where water needs are important. However, there are obstacles to pipe leaks that cause this water distribution to be hampered. The development of the Internet of Things is the main solution in terms of monitoring water flow and water pressure in pipes. This makes it easier for pipe repair parties to increase the effectiveness of their supervision of the condition of their housing pipes. Based on the results of trials and evaluations that have been carried out, it gives the conclusion that the existence of this system can help pipe repair parties in knowing the state of water flow in pipe installations in their residential areas. This system is also supported by using the calculation of physical formulas such as the Bernoulli equation and the principle of continuity where the formula P = 1/2ρV² has been used in the calculation of calibration on the water flow sensor and to test the validation of the results issued by the water flow sensor, the Absolute Relative Error calculation is also used where the formula used is Absolute Relative Error = | (estimated - actual) / actual | * 100. Through the calculation processes carried out, it can increase the chances of reading data that is more accurate than usual and the results will be maximized in detecting any anomalies that occur during monitoring. Therefore, the opportunity to implement a residential pipe monitoring system is a convincing thing to do in improving services that are more responsive to residents in the housing complex.